TVET advocacy: ensuring multi-stakeholder participation - Sgarzi, Matteo [Verfasser] (UNESCO-UNEVOC International Centre for Technical and Vocational Education and Training, 2021)
"This volume addresses the role of meso-level TVET stakeholders in the process of maintaining and updating TVET systems to ensure they remain fit for purpose. Meso-level stakeholders indicate institutions participating in the advancement of TVET systems. Of particular note in this document are organizations covering activities in specific economic sectors, such as business membership organizations (BMOs), trade unions, joint organizations or chambers of commerce, industry or crafts. This volume is intended to give meso-level TVET stakeholders a better understanding of their role in the greater TVET ecosystem; potential tools for identifying, integrating and implementing NQCs for a TVET system; and action items for closer collaboration with other stakeholders. Readers are encouraged to explore the two other BILT NQC volumes for additional insights: ‘TVET governance: steering collective action’ targets macro-level stakeholders, while ‘TVET delivery: providing innovative solutions’ focuses on micro level stakeholders." (Publisher's abstract ; BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; S 3.5.4 Sozialpartner; S 3.4.2 Industrie- und Handelskammern; 370; 330; Berufsbildung; Internationale Zusammenarbeit; Berufsbildungssystem; Sozialpartner; Industrie- und Handelskammer; Handwerkskammer; Gewerkschaft; Qualifikationsentwicklung; Kompetenzentwicklung